How to Create Human Super Civilization - Antonov, Alexander Alexandrovich (New Ideas Concerning Science and Technology Vol. 6, 2021)
Theoretical and experimental evidence of physical reality of imaginary numbers using interpretation of Ohm’s law for electrical AC circuits proposed in 1897 by Steinmetz was presented. Other pieces of evidence are mentioned as well. The use of the general scientific principle of the physical reality of imaginary numbers allowed to prove that the relativistic formulas in the existing version of the special relativity theory are wrong, as well as to deny the principle of non-exceeding the speed of light and the hypothesis of Monoverse. Corrected relativistic formulas are given and on their basis a theory of hidden Multiverse is proposed, parallel universes of which are mutually invisible. It explains why they are invisible and how these invisible universes can be seen. Using data obtained by the spacecrafts WMAP and Planck, it is proved that the hidden Multiverse has a quaternion structure, exists in the six-dimensional space, and forms Hyperverse together with other Multiverses. It is shown that the parallel universes of the hidden Multiverse are continuously drifting in multidimensional space, touch each other in many places and are even partially immersed in each other, forming portals. It is argued that the search for extraterrestrial civilizations in the solar system and even in distant space is meaningless, since you can even walk to the invisible parallel universes adjacent to our visible universe through portals, the entrances to which on Earth are anomalous zones. Moreover, extraterrestrial super civilizations have already found us long time ago and are located on Earth. The attempts to contact these super civilizations are meaningless as well, because such contacts are possible only at their wish. Consequently, to make the contacts possible, we need to convince super civilizations that human civilization is of interest to them and that it has a sufficiently high intelligence. It is shown how the human super intelligence over can be realized.